2015
DOI: 10.1159/000436997
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Sleep Duration and Non-Alcoholic Fatty Liver Disease among Japanese Men and Women

Abstract: Objective: To examine the relationship between sleep duration and non-alcoholic fatty liver disease (NAFLD). Methods: We evaluated 3,968 subjects who underwent health check-ups from June 2012 to May 2013 at the Watari Hospital Health Center in Fukushima Prefecture in Japan. Fatty liver was detected by ultrasonography. Sleep duration and lifestyle factors were estimated using a questionnaire. Sleep duration was categorized into the following groups: ≤6, 6 to ≤7, >7 to ≤8, and >8 h. The four sleep duration group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 29 publications
3
55
0
5
Order By: Relevance
“…Subsequently, a longitudinal community-based cohort study conducted in Japan demonstrated that, as compared to those who slept 7-8 h, short sleep duration (6 hours) was related to reduce risk of NAFLD in men, while this association was not significant among women (20). The late cross-sectional Japan study found that short sleep duration tends to be associated with NAFLD in women (21). Altogether, the current epidemiologic evidence does not allow for conclusive inferences in favor of a causal link between sleep duration and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a longitudinal community-based cohort study conducted in Japan demonstrated that, as compared to those who slept 7-8 h, short sleep duration (6 hours) was related to reduce risk of NAFLD in men, while this association was not significant among women (20). The late cross-sectional Japan study found that short sleep duration tends to be associated with NAFLD in women (21). Altogether, the current epidemiologic evidence does not allow for conclusive inferences in favor of a causal link between sleep duration and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the effect of long sleep duration on FLD risk. By combining three independent datasets from the two studies1213 (including 10,329 subjects), we showed that compared to normal sleep duration (5~7 hours), long sleep duration did not increase or decrease the risk of FLD (the pooled OR = 1.01, 95% CI = 0.72–1.41). The heterogeneity among studies was moderate ( P heterogeneity  = 0.110, I 2  = 54.7%) (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…ORs and 95% CIs extracted from individual studies were adjusted by age and other covariates. Four studies10111314 reported results separately by sex and one16 reported by obstructive sleep apnea (OSA) status. Thus, we treated them as independent datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations